Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kota Bukittinggi - Rossa Linda Irsa; Ramdani Bayu Putra; Nila Pratiwi; Hasmaynelis Fitri (CV. ITTC INDONESIA, 2025)
This research aims to determine how much influence Communication and the Work Environment have on Employee Performance with Work Motivation as an Intervening Variable in the Public Works and Spatial Planning Department of Bukittinggi City. The population in this study amounted to 61 respondents. The sample selection technique used a saturated sample and obtained a sample of 61 respondents. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. The results of data analysis obtained: (a) Communication has a positive and significant effect on work motivation. (b) The work environment has a negative and insignificant effect on work motivation. (c) Communication has a positive and significant effect on employee performance, (d) the work environment has a positive and insignificant effect on employee performance (e) work motivation has a negative and insignificant effect on employee performance, (f) communication has a negative and insignificant effect on employee performance through work motivation (g) the work environment has a positive and insignificant effect on employee performance through work motivation.